2010
DOI: 10.1007/s00442-010-1619-z
|View full text |Cite
|
Sign up to set email alerts
|

King eiders use an income strategy for egg production: a case study for incorporating individual dietary variation into nutrient allocation research

Abstract: The use of stored nutrients for reproduction represents an important component of life-history variation. Recent studies from several species have used stable isotopes to estimate the reliance on stored body reserves in reproduction. Such approaches rely on population-level dietary endpoints to characterize stored reserves ("capital") and current diet ("income"). Individual variation in diet choice has so far not been incorporated in such approaches, but is crucial for assessing variation in nutrient allocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…For example, Oppel et al (2010) investigated capital vs. income breeding in King Eiders (Somateria spectabilis), and Hobson et al (2011a) used identical Bayesian approaches to examine isotope data on eggs and body tissues of the High Arctic Greater Snow Goose (Chen caerulescens atlantica) population used by Gauthier et al (2003) and of two sub-Arctic populations of Lesser Snow geese (Chen caerulescens caerulescens). Both studies provided a sensitivity analysis over a wide range of assumed endogenous to egg d 15 N discrimination values.…”
Section: Tracing Nutrients To Reproductionmentioning
confidence: 99%
“…For example, Oppel et al (2010) investigated capital vs. income breeding in King Eiders (Somateria spectabilis), and Hobson et al (2011a) used identical Bayesian approaches to examine isotope data on eggs and body tissues of the High Arctic Greater Snow Goose (Chen caerulescens atlantica) population used by Gauthier et al (2003) and of two sub-Arctic populations of Lesser Snow geese (Chen caerulescens caerulescens). Both studies provided a sensitivity analysis over a wide range of assumed endogenous to egg d 15 N discrimination values.…”
Section: Tracing Nutrients To Reproductionmentioning
confidence: 99%
“…Among waterfowl, the large-bodied eiders have been considered to be capital breeders (Parker and Holm 1990, Kellet and Alisauskas 2000, Nolet 2006, Bentzen et al 2008; however, evidence is mounting that previous assumptions regarding the life-history characteristics of migratory birds may need to be revisited. This is especially true for assumptions of capital breeding because this lifehistory strategy is likely less common in migratory birds than previously believed (Gauthier et al 2003, Oppel et al 2010, Sénéchal et al 2011, Sharp et al 2013. The relative importance of nutrients derived from the breeding vs. wintering grounds is crucial for predicting how the breeding success of migrating birds responds to changes in food availability during any part of their annual cycle.…”
Section: Introductionmentioning
confidence: 92%
“…While it has been reported that Brent geese (Branta bernicla) forage an average of 3 hours a day, data on the specific amount of time most waterfowl spend foraging is lacking [64]. Ducks may not use a foraging device if the food is too difficult to obtain.…”
Section: Foraging Enrichmentmentioning
confidence: 99%